LETHAL WHITE - Galbraith, Robert (New York, NY : Mulholland Books / Little, Brown and Company, 2018)
When Billy, a troubled young man, comes to private eye Cormoran Strike's office to ask for his help investigating a crime he thinks he witnessed as a child, Strike is left deeply unsettled. While Billy is obviously mentally distressed and cannot remember many concrete details, there is something sincere about him and his story. Trying to get to the bottom of Billy's story, Strike and his partner set off on a twisting trail that leads them through the backstreets of London, into a secretive inner sanctum within Parliament and to a sinister manor house deep in the countryside. And during this labyrinthine investigation, Strike's own life is far from straightforward. His partner, Robin, is now invaluable to him in his business, but their personal relationship is much more tricky than that.
Keywords: Strike, Cormoran (Fictitious character) -- Fiction; Private investigators -- Fiction -- England; Witnesses -- Fiction; Criminal investigation -- Fiction; Manors -- Fiction -- England; Man-woman relationships -- Fiction; Detective and mystery fiction